Clinical and Hematological Profiling of Dengue Fever: Impact of Age, Gender, and Comorbidities on Disease Severity - Noman, Muhammad; Rizvi, Syeda Ruhma; Talib, Amna; Younas, Hafiza Sania; Khan, Maryam Saeed; Aybk, Urwah; Khalid, Momina; Hussain, Munir (Indus Journal of Bioscience Research, 2025)
This study analyzed 280 dengue patients (77.8% male, 22.1% female) with a median age of 30 years. The highest incidence occurred in the 40–60 age group (53%). Dengue fever (DF) was predominant (229 cases), while dengue hemorrhagic fever (DHF) affected 51 patients, with males showing higher infection rates (p=0.03). DHF patients were younger (median age 24.5 vs. 30 years) and exhibited severe symptoms like abdominal pain, rash, and elevated liver enzymes (AST/ALT levels 10x and 2.5x higher, respectively; p<0.05). Thrombocytopenia (<69,000 cells/mm³) was significant in DHF (p=0.001). Common symptoms included myalgia (91%), headache (80%), and vomiting (52.5%). Hemorrhagic manifestations (e.g., epistaxis, melena) occurred in 50% of patients. Comorbidities (e.g., hepatitis C, diabetes) worsened outcomes, increasing DHF risk (32% vs. 20%; p=0.01) and mortality (CFR=2.5%). Serological testing confirmed positivity for NS1 (41.7%), IgG (30%), and IgM (27.8%).